1988
DOI: 10.2105/ajph.78.6.704
|View full text |Cite
|
Sign up to set email alerts
|

Urban hospital cesarean section delivery rates in Paraíba State, Brazil, 1977-81.

Abstract: Parafba State, Brazil is one of the poorest areas in that country; many of the hospitals are not high quality and medical training is not comparable to that of developed countries. Nevertheless, the rate of cesarean section delivery in urban hospitals has risen from 19.0 per cent in 1977 to 28.5 in 1981. Despite the larger volume of obstetric services in government hospitals, these hospitals had lower cesarean section rates than private hospitals, both profit and non-profit. (Am J Public Health 1988; 78:704-70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Wagner 45 argued that caesarean rates are higher when maternity care is characterised by medical hegemony and midwives are marginalised. It has been widely reported that caesarean rates of private health institutions are greater than those of public one 8,16,17,22,25,28–30 . In addition, a Chilean study found that a drive toward the privatisation of health care may have had deleterious effects on the caesarean rates 46 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wagner 45 argued that caesarean rates are higher when maternity care is characterised by medical hegemony and midwives are marginalised. It has been widely reported that caesarean rates of private health institutions are greater than those of public one 8,16,17,22,25,28–30 . In addition, a Chilean study found that a drive toward the privatisation of health care may have had deleterious effects on the caesarean rates 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found a negative or no relationship between caesarean section and education 27,29 or income 21,27 . In addition, private health institutions reportedly had higher caesarean rates than public ones 8,16,17,22,25,28–30 . However, with the exception of some reports, 26,29 research regarding trends in the relationship between mode of delivery and its correlates has been scarce.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether or not this can be explained by medical considerations is not clear. Because caesarean section in Brazil in general and Paraiba in particular is very high (Rodrigues, 1988;Barros, Vaughan & Victora, 1986) women with a third or fourth caesarean section will often be sterilised for medical reasons.…”
Section: Resultsmentioning
confidence: 99%
“…The number of patients under obstetric treatment in private hospitals may have decreased, but length of stay may have increased taking into consideration that the Caesarian section rate has been increasing over the year. It has been claimed that Brazil has the highest Caesarian section rate in the world: financial incentives seem to be influencing this medical procedure (Rodrigues, 1988; Barros et al, 1986;Lins and Fortney, 1981). Table 4 shows the variations in inpatient care from 1980 to 1986 across the three most populated regions in Brazil, which have accounted for approximately 90 percent of all hospitalizations.…”
Section: Rate Of Discharges Per 1 Ooo Popuation Regionmentioning
confidence: 99%